Topos og motiv. Et forskningshistorisk rids - Dahl, Christian (K&K - Kultur og Klasse, 2017)
The aim of this article is to clarify how literary topology relates historically and conceptually to the study of literary motifs. Topos and motif are associated concepts in literary theory, but attempts to define and compare them are evasive and few. While literary topology was, according to Ernst Robert Curtius, founded on the basis of classical rhetoric and concerned primarily the literary tradition of rhetorical eloquence, the notion of motif was, as I will argue, on the contrary conceived as a critical term at a time when rhetoric was loosing its grip on literary criticism at the end of the 18th century. My article will survey a number of influential positions in the history of literary theory and criticism concerning the study of motifs and topoi from Goethe to contemporary contextualist approaches.